Sustainability in Higher Education: Analysis and Selection of Assessment Systems - Maragakis, Antonios; van den Dobbelsteen, Andy (A+BE | Architecture and the Built Environment, 2018)
There is a noticeable increase in interest with regards to sustainability in higher education. As institutions investigate, implement and market sustainability efforts, there is a myriad of sustainability assessment methodologies currently available. Although these assessment systems were created with the intention of helping sustainability in higher education institutions, they have ultimately led to an assortment of standards being used by institutions which do not help students and faculty assess the level of sustainability uniformly between institutions. This paper combines relevant literature on sustainability assessment with empirical data to suggest an ideal assessment method to be used as the basis for a universal tool. It was found that the STARS system was the most suited system to be used as a basis for a future universal assessment tool.